Article RETRACTED due to malpractice Digital Leadership in Sports Education: AI-Driven Approaches to Inclusive Teaching and Learning - sen, Rimmi (Retos, 2026)
This research paper looks at how digital leadership and Artificial Intelligence (AI) are changing sports education by making teaching and learning more inclusive. The main purpose of this study is to see how leaders can use AI tools not just for better performance tracking but also for fairness, psychological comfort, and equal opportunities in sports classrooms. The paper uses secondary data as its method, which means it brings together evidence from books, journal articles, and case studies. This helped to collect wide information, save time, and compare results across different studies. The findings showed four key results. First, AI-enabled assessment tools improve participation and give fair feedback to all students, including those with disabilities. Second, digital leadership plays a big role in making sure technology is used in the right and strategic way. Third, human-centered leadership improves psychological comfort, reduces stress, and increases motivation for students and teachers. Fourth, organizational adaptability is very important for the success of AI teaching models, because institutions that adjust quickly to change use AI more effectively. Overall, this research shows that technology alone cannot improve education. It needs strong leadership, emotional intelligence, and adaptability. The study proves that when AI tools are guided by digital leaders who focus on people, sports education becomes fairer, more modern, and inclusive. This paper gives a clear direction for schools and organizations that want to use AI in a way that benefits every learner equally.